005.6 Distinct growth and genome profiles are present in clinical isolates from women who fail to resolve genital chlamydia infection after azithromycin treatment. (13th September 2015) - Lawrence, A; Hocking, JS; Wee, B; Vodstrcil, L; Timms, P; Tabrizi, S; Huston, WM
Abstract : Introduction: Treatment failure to be appears to occurring in women with genital Chlamydia trachomatis after azithromycin treatment. This study aimed to characterise the molecular basis of treatment failure by characterising clinical isolates from these women who failed to resolve the infection. Methods: A selection of 6 clinical isolates were cultured and whole genome sequence examined. Cultures were conducted in variety of cell lines, and in the presence of a novel anti-chlamydial drug to examine differences in growth and drug responses between isolates from treatment failure cases and treatment resolved cases. Results: The clinical isolates showed distinct growth profiles in different cell lines, with variation in infectious progeny yield and kinetics. Cervical, endometrial, gastrointestinal and fibroblast cell lines were compared and distinctions in growth were observed. There were no genome mutations in the ribosome loci in any isolate that would confer a direct resistance to azithromycin. However, there was less susceptibility to a novel anti-chlamydia drug by a clinical isolate from a treatment failure case as well as higher growth yield in the absence of the drug. Conclusion: Distinct phenotypic growth traits were observed in clinical treatment failure isolates of C. trachomatis that could underlie the mechanism of azithromycin treatment failure clinically. Disclosure of interest statement: This study was funded by the NHMRC.